2013
DOI: 10.1111/adb.12058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naltrexone plus topiramate on ethanol self‐administration and tyrosine hydroxylase gene expression changes

Abstract: The purpose of this study was to evaluate the effects of naltrexone (0.7 mg/kg) and/or topiramate (25 mg/kg) on ethanol consumption and the motivation to drink in an oral-operant conditioning paradigm in C57BL/6 mice. Subsequent real-time polymerase chain reaction (PCR) experiments were performed to analyze gene expression changes in tyrosine hydroxylase (TH) in the ventral tegmental area (VTA). The administration of naltrexone significantly reduced ethanol consumption and the motivation to drink during the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 54 publications
1
27
2
1
Order By: Relevance
“…Navarette et al (2013) demonstrated that this combination reduced tyrosine hydroxylase in the ventral-tegmental area further than either alone, while simultaneously reducing ethanol reinforcement suggesting that its efficacy may be due to its effects on ethanol-mediated dopamine release within the mesolimbic pathway. Tyrosine hydroxylase has also been shown to be upregulated after chronic ethanol exposure (Ortiz et al 1995), along with the dysfunction of other pathways, such as GABA and opioid peptides that occur in this allosteric state (Koob, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Navarette et al (2013) demonstrated that this combination reduced tyrosine hydroxylase in the ventral-tegmental area further than either alone, while simultaneously reducing ethanol reinforcement suggesting that its efficacy may be due to its effects on ethanol-mediated dopamine release within the mesolimbic pathway. Tyrosine hydroxylase has also been shown to be upregulated after chronic ethanol exposure (Ortiz et al 1995), along with the dysfunction of other pathways, such as GABA and opioid peptides that occur in this allosteric state (Koob, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…The combination of topiramate and ondansetron has also been reported to effectively reduce ethanol consumption in heavy drinking rats, with better efficacy of the combination than either alone for reducing relapse behavior (Lynch et al 2011). Additionally, the combination of topiramate and naltrexone was found to reduce ethanol self-administration in mice under limited-access conditions (Navarrete et al 2013). Here, we found the combination of naltrexone and topiramate reduced both ethanol consumption and reinforcement in models of prolonged ethanol access, with better efficacy of the combination than either alone for reducing ethanol consumption, and better efficacy than topiramate alone for reducing ethanol reinforcement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the changes in dopamine levels are well known, the acute effect of ethanol on the expression of tyrosine hydroxylase (TH), the rate-limiting enzyme in dopamine synthesis, is not well-understood, with some evidence reporting an increase in th mRNA levels (Oliva et al, 2008). A chronic treatment with ethanol has been shown to increase th mRNA levels in the rat brain (Lee et al, 2005; Navarrete et al, 2013), but there is also evidence suggesting that TH protein levels decrease after chronic ethanol treatment (Kashem et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…This opioid antagonist has previously been shown to decrease mouse operant responding maintained by EtOH (Middaugh et al 1999b; Navarrete et al 2013) and mouse EtOH intake during DID and two-bottle choice paradigms (Phillips et al 1997; Kamdar et al 2007). In the absence of any effect on water vehicle controls, naltrexone was effective at inhibiting 15% EtOH in water intake at sub-intoxicating doses consistent with its therapeutic profile in alcoholics.…”
Section: Discussionmentioning
confidence: 99%